PENGARUH PELATIHAN ASSERTIVE CLASSROOM MANAGEMENT UNTUK KESIAPAN MENGAJAR MAHASISWA KEGURUAN PROVINSI KALIMANTAN TENGAH - Wulan, Riwu; Ediyanto, Ediyanto (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
The purpose of this research is to identify the effect of Assertive Classroom Management training on teacher readiness among teacher education students at universities in the Ministry of Religious Affairs of Central Kalimantan Province.The research method employed in this study is quantitative, and the type of research used is experimental. Experiments in this study are included in the pre-experiment type with a single-group pretest-posttest experimental design. The research was conducted within five months, from June to October 2019. This research was carried out in all State Religious Higher Education Institutions located in Palangka Raya City, Central Kalimantan, with a total population of 185 people.Based on the t-test results of both the pretest and posttest data analysis, it is possible to conclude that Assertive Classroom Management training has a substantial effect on prospective teachers' teaching readiness at universities in the Ministry of Religion of Central Kalimantan Province. Students who receive Assertive Classroom Management training have higher readiness after the training than before the training.